Infusing public service motivation (PSM) throughout the employment relationship: a review of PSM and the human resource management process - Piatak, Jaclyn S.; Sowa, Jessica E.; Jacobson, Willow S.; McGinnis Johnson, Jasmine (International public management journal, 2020)
Employees are essential for the effective delivery of public services. Interest in human resource management (HRM) has increased, yet we still have much to learn about the contextually specific aspects of the HRM process in public and nonprofit organizations-how these functions work, what are model practices, and how practices are shaped by organizational and job contexts in the public service. At the same time, research on public service motivation (PSM) has rapidly expanded to understand the unique drive of individuals to serve the public, but like HRM, there are many debates and questions that remain unanswered. We discuss challenges facing both HRM and PSM research and call for a greater examination of PSM in the context of HRM. We do so by focusing on two aspects of the HRM process - job design and recruitment and selection - to see what lessons we have learned from PSM research to date in these areas and what questions arise with avenues for future research to connect PSM and HRM to inform research and practice. We know HRM matters and we know PSM matters but we know little about whether or how to incorporate PSM into HRM processes, policies, and practices.